Design, synthesis, in vitro antiproliferative evaluation, and kinase inhibitory effects of a new series of imidazo[2,1-b]thiazole derivatives - Abdel-Maksoud, Mohammed S.; Kim, Mi-Ryeong; El-Gamal, Mohammed I.; El-Din, Mahmoud M. Gamal; Tae, Jinsung; Choi, Hong Seok; Lee, Kyung-Tae; Yoo, Kyung Ho; Oh, Chang-Hyun (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2015)
Design and synthesis of a new series of 5,6-diarylimidazo[2,1-b]thiazole derivatives possessing terminal aryl sulfonamide moiety are described. Their in vitro antiproliferative activities against a panel of 57 human cancer cell lines of nine different cancer types were tested at the NCI. Compounds 8a, 8b, 8n, 8q, 8t, and 8u showed the highest mean % inhibition values over the 57 cell line panel at 10 mu M, and they were further tested in 5-dose testing mode to determine their IC50 values. Among the six compounds, compound 8u possessing terminal para-hydroxybenzenesulfonamido moiety and ethylene linker showed the highest potency. It demonstrated superior potency than Sorafenib against eight different cell lines, and was equipotent to Sorafenib against COLO 205 colon cancer cell line. Its IC50 values over NCI-H460 non-small cell lung cancer cell line and MCF7 breast cancer cell line were 0.845 mu M and 0.476 mu M respectively. Compounds 8a, 8b, 8q, 8t, and 8u showed high selectivity indices towards cancer cells over L132 normal lung cell line. Compound 8u showed potential inhibitory effects over the components of ERK pathway. Its IC50 value over V600E-B-RAF and C-RAF kinases were 39.9 nM and 19.0 nM, respectively. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: POTENTIAL ANTITUMOR AGENTS; ANTICANCER EVALUATION; EXPRESSION; PROTOONCOGENE; CANCER; RAF-1